Biogenesis of Outer Membrane Vesicles Concentrates the Unsaturated Fatty Acid of Phosphatidylinositol in Capnocytophaga ochracea - Naradasu, Divya; Miran, Waheed; Sharma, Shruti; Takenawa, Satoshi; Soma, Takamitsu; Nomura, Nobuhiko; Toyofuku, Masanori; Okamoto, Akihiro (Frontiers in Microbiology, 2021)
Bacterial outer membrane vesicles (OMVs) are spherical lipid bilayer nanostructures released by bacteria that facilitate oral biofilm formation via cellular aggregation and intercellular communication. Recent studies have revealed that Capnocytophaga ochracea is one of the dominant members of oral biofilms; however, their potential for OMV production has yet to be investigated. This study demonstrated the biogenesis of OMVs in C. ochracea associated with the concentration of unsaturated fatty acids of phosphatidylinositol (PI) and characterized the size and protein profile of OMVs produced at different growth phases. Transmission electron microscopy showed isolated spherical structures from cells stained with heavy metals, indicating the production of OMVs with a size ranging from 25 to 100 nm. Lipidome analysis revealed the presence of phosphatidic acid, phosphatidylethanolamine, phosphatidylcholine, and PI as the main lipids. Some unsaturated fatty acids of PI were present specifically in OMV and little in the outer membrane, suggesting that OMVs are generated from a specific region of the membrane through blebbing rather than a random process such as cell lysis. Furthermore, the lack of similar PI accumulation in the OMV of Porphyromonas gingivalis suggests that C. ochracea has a different biogenesis mechanism. The blebbing mechanism was further supported by higher OMV production occurring at the exponential phase in comparison to the stationary phase, where cell lysis is more likely to occur. Further, comparative protein profile of OMVs isolated under different growth phases may indicate that the OMV cargo does not largely vary with different growth phases. The present study provides a basis for further understanding the roles of C. ochracea OMVs in oral biofilms as well as systemic diseases that C. ochracea involves.